A systems approach to the assessment of organization the General Office, Bureau of Public Schools - Sutaria, Minda (Cascolan)
This study aims to determine the indices of organizational performance and develop a scale for measuring it, and to test the scheme evolved for assessing organizational functioning or health on a public organization, the General Office, Bureau of Public Schools. Manila. The three directors. 17 division/unit chiefs and their respective divisions constituted the subjects of the study. 402 respondents drawn at random from the 17 divisions/units and the office staffs of the three directors were involved. The research instruments used are the Leadership Behavior Description Questionnaire-1957 (LBDQ), the Organizational Climate Description Questionnaire (OCDQ), and the Organizational Performance Scale-4. The findings support the hypothesis that leadership style, organizational climate, and organizational performance are critical indicators of organizational functioning or health. The research evidence indicates a positive relationship between leadership style and organizational climate and between organizational climate and organizational performance, but no significant relationship between leadership style and organizational performance.